2005
DOI: 10.1073/pnas.0504430102
|View full text |Cite
|
Sign up to set email alerts
|

Avicinylation (thioesterification): A protein modification that can regulate the response to oxidative and nitrosative stress

Abstract: Avicins are a recently discovered family of plant-derived terpenoid molecules that possess proapoptotic, antiinflammatory, and cytoprotective properties in mammalian cells. Previous work demonstrating that avicins can exert their effects by suppressing or activating the redox-sensitive transcription factors NF-B and nuclear factor-erythroid 2 p45-related factor (Nrf2), respectively, has raised the idea that they may react with critical cysteine residues. To understand the molecular mechanism through which avic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
(38 reference statements)
3
41
0
Order By: Relevance
“…Initially, this was based primarily on in vitro studies indicating that oxidative modification of only C199 was sufficient for activation, since hydroxylated Cys199-SOH, S-nitrosylated (Cys199-SNO), and S-glutathionylated (Cys199-S-S-G) forms of OxyR were able to activate transcription, and that the different modifications elicited distinct changes in the circular dichroism (CD) spectra of OxyR-DNA complexes (40,56). The idea was subsequently reinforced by the observation that Cys199-thiol-esterification of OxyR resulted in activation of target genes both in vitro and in vivo (38). Until recently, there were little available data to adequately evaluate the molecular code model's prediction of modification-specific patterns of gene activation.…”
Section: Oxyrmentioning
confidence: 98%
“…Initially, this was based primarily on in vitro studies indicating that oxidative modification of only C199 was sufficient for activation, since hydroxylated Cys199-SOH, S-nitrosylated (Cys199-SNO), and S-glutathionylated (Cys199-S-S-G) forms of OxyR were able to activate transcription, and that the different modifications elicited distinct changes in the circular dichroism (CD) spectra of OxyR-DNA complexes (40,56). The idea was subsequently reinforced by the observation that Cys199-thiol-esterification of OxyR resulted in activation of target genes both in vitro and in vivo (38). Until recently, there were little available data to adequately evaluate the molecular code model's prediction of modification-specific patterns of gene activation.…”
Section: Oxyrmentioning
confidence: 98%
“…Moreover, the treatment of cells with dithiothreitol (DTT) could reverse the avicin G-induced inhibition in DNA binding of NF-kB complex. This is due to the ability of avicins to cause thioesterification, also called avicinylation, of the cysteine residue in the DNA-binding domain of the NF-kB protein [122]. The amount of avicin in plants is dependent on stress insults, and hence different stress models in in vitro cultures have been established to achieve biomass production of avicins.…”
Section: Avicinsmentioning
confidence: 99%
“…Recent studies have shown that the sulfinic acid form of 2-cys peroxiredoxins can be reduced back to the sulfhydryl in an ATP-dependent enzyme-(sulfiredoxin, Srx) catalyzed reaction [39], and a reversible thioesterifcation has been reported to alter transcriptional activity [40], raising the possibility that additional Cys modifications may be found to have regulatory roles. Cysteines also are uniquely targeted by alkylating species (such as cyclopentenone prostaglandins, acrolein), hydroxynonenal and avicins (which can be formed endogenously, or encountered through environmental insults [41,42]), and by acylation (which has important roles in localizing proteins to the membranes [43]).…”
Section: Oxidizable Amino Acids: Reactive Cysteines As Redox Targetsmentioning
confidence: 99%